“Anti-Texture” Agents in the Written English Essays of Students in a Ghanaian University - Amoakohene, Benjamin; Akoto, Osei Yaw; Siame, Pethias; Kapau, Humphrey (ELT Worldwide: Journal of English Language Teaching, 2024)
Texture proves to be a key indicator for measuring the quality of a text but establishing this text quality is a challenge for most English as a Second Language (ESL) students. This challenge has led to an array of studies to find the root cause(s) of this/these writing challenge(s) of ESL students. Despite these numerous studies, there is still paucity of research on “anti-texture” agents in the written English essays of students from the Ghanaian context, especially those at the tertiary level. In filling this gap, this study uses Halliday and Hasan’s (1976) cohesive theory as a framework to explore the types of cohesive errors that serve as “anti-texture” agents in 150 written English essays of students from a Ghanaian university. Because of the highly descriptive nature of this current investigation, it uses the qualitative content analysis as its design. The findings show that challenges like unclear pronoun references, wrong selection of cohesive devices, over usages of one cohesive device within the same textual environments, wider textual distances between references and their referents, the omission of cohesive devices, wrong insertions of cohesive devices and references lacking referents served as barriers to ESL students quest to use cohesive devices as means of creating texture in their texts. The findings further confirmed that the inappropriate use of cohesive devices in the students’ essays disrupted the free flow of information and as such, rendered the essays incoherent. The study has pedagogical implication for ESL academic writing instructors and curriculum developers.